Dr. Autar Krishen Mattoo (1943-2024): an outstanding plant biologist with a focus on photosynthesis - A.K. HANDA; M. EDELMAN; W.W. ADAMS III; G. GOVINDJEE (Photosynthetica, 2025)
We provide here the academic life of Dr. Autar Krishen Mattoo (1943-2024), including his role as a research leader at the United States Department of Agriculture and his outstanding contributions in photosynthesis, plant physiology and molecular biology with a focus to enhance nutrients. His work included ways to regulate Photosystem II (PSII) reaction center proteins, as well as to exploit, for our benefit, the role of polyamines in the plant world. Further, he provided the basis for beneficial aspects of sustainable agriculture systems and for selecting genes/proteins that provide better growth, higher disease resistance, and tolerance from abiotic stress. Autar K. Mattoo was a true international scholar and leader. We include below an overview of his selected research, his wonderful association with others, as well as a few reminiscences.